Entre o corpo da obra e o corpo do observador - Coelho, Ricardo [UNESP] (2015)
Since the first expressive demonstrations of humanity, the human body is certainly the most recurrent subject in the history of representations in the West, from the 6th century B.C in Greece to Contemporary Art, period approached of synchronous mode in this study. Our main objective was to analyze the relations established between the body of the work (always taken as a representation) and the body of the observer at the time of the aesthetic fruition. This relationship inherent to the artistic phenomenon, changes in each context, depending of a complex network of meanings, which are not restricted to the specificities of expressive languages. Therefore, it was important to consider the fact that the space between the body of the work and the body of the observer - as well as the space that separate the reader (observer) and this text (work) at the moment - is also virtually filled by their personal experiences and the several representations, which make the body in the complex sociocultural setting. In other words, more than specific representations of visual arts field, it was necessary to consider and to approach some of the multiple dimensions of culture, expressed in social, political, religious, legal, medical, scientific and sexual representation of the body. This decision is due to our consideration that there is a virtual space inhabited by their personal experiences and by other representations produced in the cultural universe between the observer and any work. The body through its feelings, the work on its autonomy and the space, full of sliding meaning, form an organic and complex network, as if we were the center of a city where local interactions can lead to a more complex global order